The Effectiveness of Using Instagram as Information Media at Modern Islamic Boarding School Darussalam Gontor - Alfiananadra Wafiq Pradana; Mohammad Luthfi (Sahafa Journal of Islamic Communication, 2024)
The existence of public relations of pesantren has an important role in maintaining and increasing public trust through various communication activities. Instagram is a digital platform that is widely used by pesantren to disseminate information and as a medium of communication with their public. This research measures the effectiveness of Instagram as an information medium for Pondok Modern Darussalam Gontor through a quantitative approach with a descriptive survey method referring to the 4C theory with 4 measurement indicators, namely context, communication, collaboration connection. Data was collected through a questionnaire distributed to 400 samples as respondents from 156,631 followers @pondok.modern.gontor as the research population. Data analysis uses the frequency distribution formula and Likert Summated Rating. The results of the research show that the use of Instagram as an information medium for Pondok Modern Darussalam Gontor is considered very effective as indicated by a score of 20,312 in the range >Q3 to A. Theoretically, this research provides implications in the development of the 4C theory, and also contributes practically to the use of Instagram as a organizational information media, especially for pesantren. Keywords : Instagram, Information Media, Pesantren